SARS-CoV-2 ORF3a accessory protein is a water-permeable channel that induces lysosome swelling - Antonio Michelucci; Luigi Sforna; Riccardo Focaia; Maria Vittoria Leonardi; Angela Di Battista; Giorgia Rastelli; Simone Vespa; Simona Boncompagni; Manlio Di Cristina; Luigi Catacuzzeno (Communications Biology)
Abstract ORF3a, the most abundantly expressed accessory protein of SARS-CoV-2, plays an essential role in virus egress by inactivating lysosomes through their deacidification. However, the mechanism underlying this process remains unclear. While seminal studies suggested ORF3a being a cation-selective channel (i.e., viroporin), recent works disproved this conclusion. To unravel the potential function of ORF3a, here we employed a multidisciplinary approach including patch-clamp electrophysiology, videoimaging, molecular dynamics (MD) simulations, and electron microscopy. Preliminary structural analyses and patch-clamp recordings in HEK293 cells rule out ORF3a functioning as either viroporin or proton (H+) channel. Conversely, videoimaging experiments demonstrate that ORF3a mediates the transmembrane transport of water. MD simulations identify the tetrameric assembly of ORF3a as the functional water transporter, with a putative selectivity filter for water permeation that includes two essential asparagines, N82 and N119. Consistent with this, N82L and N82W mutations abolish ORF3a-mediated water permeation. Finally, ORF3a expression in HEK293 cells leads to lysosomal volume increase, mitochondrial damage, and accumulation of intracellular membranes, all alterations reverted by the N82W mutation. We propose a novel function for ORF3a as a lysosomal water-permeable channel, essential for lysosome deacidification and inactivation, key steps to promote virus egress.